PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NHT MENGGUNAKAN PENDEKATAN PEMBELAJARAN MENDALAM TERHADAP HASIL BELAJAR IPAS PADA SISWA KELAS V SD INPRES SAMATA - Syarfia, A. Nurul; Amal, Amri; Nurfadilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is a quasi-experimental study using a nonequivalent control group design. The variables in this study consist of the Numbered Heads Together (NHT) Cooperative Learning Model using a Deep Learning Approach as the independent variable and learning outcomes as the dependent variable. The population of this study included all fifth-grade students totaling 39 students, consisting of 20 students in the experimental class and 19 students in the control class. The data collection techniques used were tests, observation sheets, and documentation. The research instruments consisted of a learning outcomes test and observation sheets. The results of the study showed that the average post-test score in the experimental class was 84.95, while in the control class it was 79.79. The hypothesis test results showed that tcount = 2.542 > ttable = 2.02619, therefore H₁ was accepted and H₀ was rejected. Based on these results, it can be concluded that there is an effect of using the NHT Cooperative Learning Model with a Deep Learning Approach on the IPAS learning outcomes of fifth-grade students at SD Inpres Samata.